HOUSE OF ROLE AS AN EFFORT TO PROTECT CHILDREN FROM VIOLENCE: AN INDONESIAN HUMAN RIGHTS PERSPECTIVE - Sholahuddin Al-Fatih (Universitas Muhammadiyah Malang, 2021)
This research aims to discuss the children's violence that occur in Indonesia. This research using legal research, namely research conducted to produce arguments, new theories or concepts as a prescriptive in solving the problems faced. This research found that the number of cases of violence against children in Indonesia is very high and tends to increase from year to year. To overcome this, it is necessary to create a role model house, namely a house that involves 5 elements (parents, family, community, government, local and state governments) in fulfilling children's rights to prevent violence.